2017
DOI: 10.1007/s11145-017-9791-8
|View full text |Cite
|
Sign up to set email alerts
|

Lexical quality and executive control predict children’s first and second language reading comprehension

Abstract: This study compared how lexical quality (vocabulary and decoding) and executive control (working memory and inhibition) predict reading comprehension directly as well as indirectly, via syntactic integration, in monolingual and bilingual fourth grade children. The participants were 76 monolingual and 102 bilingual children (mean age 10 years, SD = 5 months) learning to read Dutch in the Netherlands. Bilingual children showed lower Dutch vocabulary, syntactic integration and reading comprehension skills, but be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 54 publications
(94 reference statements)
9
33
0
Order By: Relevance
“…This WTI-index measure is easily applicable within a school setting. Furthermore, while previous studies demonstrated what the WTI process looks like in younger children learning Dutch as an L2 (van den Bosch et al, 2018;Raudszus, Segers, & Verhoeven, 2018 and adult learners (Calloway & Perfetti, 2017;Helder et al, 2019;Stafura et al, 2015), the current study added to this body of literature demonstrating three types of integration in 7 th grade English as an L2 learners. To conclude, we provided a perspective on word-to-text integration in early English L2 learners.…”
Section: Discussionmentioning
confidence: 70%
“…This WTI-index measure is easily applicable within a school setting. Furthermore, while previous studies demonstrated what the WTI process looks like in younger children learning Dutch as an L2 (van den Bosch et al, 2018;Raudszus, Segers, & Verhoeven, 2018 and adult learners (Calloway & Perfetti, 2017;Helder et al, 2019;Stafura et al, 2015), the current study added to this body of literature demonstrating three types of integration in 7 th grade English as an L2 learners. To conclude, we provided a perspective on word-to-text integration in early English L2 learners.…”
Section: Discussionmentioning
confidence: 70%
“…In most studies, information on the participants' linguistic background was collected through interviews or questionnaires made to their caregivers. In two studies, the information was collected by directly interviewing the participants (Jalali-Moghadam and Kormi-Nouri, 2015 ; Raudszus et al, 2018 ). The analyzed studies reported different definitions of bilingualism; some of these definitions are based on the assessment of the competences in the two languages; others are founded on the age of acquisition of the two languages.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies (Danahy et al, 2007 ; Bialystok and Feng, 2009 ; Bialystok and Viswanathan, 2009 ; Bialystok, 2010 ; Engel de Abreu, 2011 ; Kapa and Colombo, 2013 ; Blom et al, 2014 , 2017 ; Engel de Abreu et al, 2014 ; Filippi et al, 2015 ; Garraffa et al, 2015 ; Buac et al, 2016 ; Cockcroft, 2016 ; Bosman and Janssen, 2017 ; Raudszus et al, 2018 ; Veenstra et al, 2018 ; Hartanto et al, 2019 ; Jaekel et al, 2019 ) evaluated working memory by using different versions of the digit span task. In 12 studies (Danahy et al, 2007 ; Bialystok and Feng, 2009 ; Bialystok and Viswanathan, 2009 ; Engel de Abreu, 2011 ; Kapa and Colombo, 2013 ; Engel de Abreu et al, 2014 ; Filippi et al, 2015 ; Garraffa et al, 2015 ; Cockcroft, 2016 ; Blom et al, 2017 ; Raudszus et al, 2018 ; Veenstra et al, 2018 ) no significant differences between the two groups emerged. In three studies, monolinguals remembered a significantly higher number of digits than bilinguals in the forward digit span task (Buac et al, 2016 ; Bosman and Janssen, 2017 ) and backward digit span (Jaekel et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also interesting to compare the findings of these studies to similar studies on L2 reading. Studies on the relative significance of lexical and syntactic knowledge in L2 reading have also yielded mixed results-some studies found a greater contribution of lexical knowledge (Bossers, 1992;Brisbois, 1995;Yamashita, 1999), while others reported heavier regression weights of syntactic knowledge (Shiotsu and Weir, 2007). Shiotsu and Weir (2007) emphasized the difference between a structural equation model and a regression model but also noted that sample size, test difficulty relative to the participants, characteristics of the participants, and the nature and reliabilities of the instruments used are important methodological factors that may explain the differences between studies.…”
Section: Comparability To Earlier Studiesmentioning
confidence: 99%